Life‐Course Reproductive History and Cardiovascular Risk Profile in Late Mid‐Life: The CARDIA Study - Lane‐Cordova, Abbi D. (J Am Heart Assoc, 2020)
BACKGROUND: Reproductive events, that is, a preterm birth (PTB), small‐for‐gestational‐age infant (SGA), and vasomotor symptoms of menopause, are associated with subclinical atherosclerotic cardiovascular disease (ASCVD). We evaluated whether women with a past PTB and/or SGA (henceforth PTB/SGA) were more likely to have severe vasomotor symptoms of menopause and whether the estimated 10‐year ASCVD risk was higher in women with PTB/SGA and vasomotor exposures. METHODS AND RESULTS: We assigned 1866 women (mean age=55±1 years) in the CARDIA (Coronary Artery Risk Development in Young Adults) study to the following categories of reproductive exposures: none, PTB/SGA only, vasomotor symptoms only, or both PTB/SGA and vasomotor symptoms. We used Kruskal‐Wallis tests to evaluate the differences in pooled cohort equation ASCVD risk scores by category and linear regression to evaluate the associations of categories with ASCVD risk scores adjusted for study center, body mass index, education, current hormone replacement therapy use, parity, and hysterectomy. Women with PTB/SGA were more likely to have severe vasomotor symptoms, 36% versus 30%, P<0.02. ASCVD risk score was higher in women with both PTB/SGA and vasomotor symptoms (4.6%; 95% CI, 4.1%–5.1%) versus women with no exposures (3.3%; 95% CI, 2.9%–3.7%) or vasomotor symptoms only (3.8%; 95% CI, 3.5%–4.0%). ASCVD risk score was higher in women PTB/SGA (4.8%; 95% CI, 3.6%–5.9%) versus no exposures. PTB/SGA and vasomotor symptoms was associated with ASCVD risk score in white women versus no exposures (β=0.40; 95% CI, 0.02–0.78). CONCLUSIONS: Women with prior PTB/SGA were more likely to have severe vasomotor symptoms of menopause. Reproductive exposures were associated with an estimated 10‐year ASCVD risk in white women.